Impressões sobre o curso de medicina da Universidade Federal de São Carlos: uma narrativa crítico-reflexiva - Oliveira, Gabriel Cuéllar (Universidade Federal de São Carlos, 2021)
Critical-Reflective Narrative that seeks to synthesize the experiences lived in the medial course at UFSCar, with a brief introduction of the general characteristics of the course followed by a chronological analysis, according to the training cycles in which the course is structured.
Impressions about the medical course os the Universidade Federal de São Carlos: a critical-reflective narrative
Keywords: Graduação; Medicina; Narrativa; Graduation; Medicine; Narrative; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM